Nicotinamide and Nonmelanoma Skin Cancers. Issue 3 (15th February 2022) - Jamison, Aaron; Malhotra, Raman
Abstract : Oral nicotinamide supplementation may have the potential to reduce the incidence of non-melanoma skin cancers, and although currently unproven, given its favorable side effect profile, supplementation should be considered seriously, particularly in high-risk individuals.